Drug war zone: frontline dispatches from the streets of El Paso and Juárez - Campbell, Howard (The William and Bettye Nowlin series in art, history and culture of the Western Hemisphere, 2009)
PART 1. SMUGGLING IN THE DRUG WAR ZONE: Introduction: Drug trafficking - studies and sources relevant to the Mexican-American drug war zone ; La Nacha: The heroin queen of Juarez ; The roots of contraband smuggling in El Paso ; Female drug lord ; Community-based drug use, smuggling, and dealing in the 1970s and 1980s ; Selling drugs in downtown Juarez: Juan and Jorge ; A young smuggler and his family ; Blaxicans: The life of a Chicano smuggler and musician on the borderline of African American and Mexican American culture ; Drug addiction and drug trafficking in the life of an anarchist ; Drug smuggling through tunnels: The tale of a scuba-diving instructor ; Witness to a Juarez drug killing -- PART 2. LAW ENFORCEMENT IN THE DRUG WAR ZONE: Introduction: Ethnographic dimensions of law enforcement in the drug war zone ; Undercover agent on the Border: Cultural disguises ; The death of Francisco ; A Juarez policeman fighting drug traffickers ; Journalism and drug trafficking: Covering the narco beat on the Border ; Patrolling the drug war zone: A Border Patrol Agent in the War on Drugs ; Intelligence and the drug war: Commander of an Antidrug Task Force on the Border ; Excerpt from Weed: Adventures of a Dope Smuggler by Jerry Kamstra ; Agent on prohibition -- Epilogue and conclusion